(untitled) (ModaPalavra e-periódico, 2008)
Adolescence is a stage of life where the individual deals with the discovery of body and where the role of clothing is imperative. To understand the complexity of appearance and the function of Fashion for teenagers, the objective of this paper is to draw a brief historical overview, using the Generation system, and the relationship of these different generations with the act of dressing. The main emphasis is in contemporary generation, characterized as Generation Y, which provides a new way of dealing with the body and Fashion. The notes show these current young people living in two realities: the virtual or symbolic, which remains an idealized image, and the physical or material, which through the role of Fashion the Teenagers bodies try to sustain the simulacrum built in cyberspace.